Classical and quantum charge density model of nano scale doped DG MOSFETs below onset of strong inversion. (13th February 2019) - Bose, Ria; Roy, J N
Abstract: Classical and quantum inversion charge density models are derived below threshold for a doped double-gate (DG) MOSFET. Since our charge density model includes a 2D analytical solution of channel potential considering the contribution of both mobile charge and doping concentration terms, the proposed models are also investigated slightly above threshold of the device having different channel lengths and validated by 2D TCAD (Technology Computer Aided Design) simulation. Quantum Confinement Effects are incorporated in quantum model by considering a 1D infinite rectangular well with a perturbation applied. Finally charge models are implemented in suitable drain current equation to study the electrical behavior of the device.